Information acceleration to improve strategic management decisions: The case of really new products. Issue 7 (17th August 2015) - Proff, Heike; Fojcik, Thomas M.
Abstract : Purpose: – Really new products (RNP) run the risk not only of technical problems in the development process, but also of problems with customer acceptance. Because market uncertainty in particular is frequently high, many top management teams defer essential management decisions on these products until sufficient information is available to be able to make a sound decision. In many cases, however, the market is already been divided up by that time. The purpose of this paper is to examine how better information about customers can be acquired by providing them with a better offering of information which has been prepared in a variety of forms ("information acceleration") and how management decisions can be improved as a result. Design/methodology/approach: – The paper is based on modern models for decision making under uncertainty that incorporate group decisions, and shows how the measurement of purchasing behavior can be improved by information acceleration in a test studio. This is needed because customers generally cannot draw on mentally established analogies in the case of RNP, so that they are virtually unable to make meaningful statements that would improve strategic management decisions when completing standard customer surveys. A test studio was set up in the form of a Car Clinic for the example of a future electric vehicle as a RNP. 121 customers were to be offered a wide variety of information (about the future urban environment, the design of the vehicle concept and the driver's experience), partly in order to acquire information about the customers. In particular, the extent to which customers could better evaluate their purchasing probability and willingness to pay certain prices and the extent to which the variance of customer opinions was reduced after attending the Car Clinic were examined, because these factors make it easier to forecast future sales revenue and management decisions can be made more easily. Findings: – The results reveal that information acceleration in a test studio can improve the estimation of sales revenue in an early decision-making phase and can have a positive influence on decision-making behavior under uncertainty. Originality/value: – This study provides an empirical, valuable step toward an investigation of management decisions on RNP under uncertainty.